Cele i zadania ogrodów zoologicznych = The objectives and tasks of zoos - Habel, Angelika; Mroczkowski, Sławomir (Journal of Education, Health and Sport, 2015)
Habel Angelika, Mroczkowski Sławomir. Cele i zadania ogrodów zoologicznych = The objectives and tasks of zoos. Journal of Education, Health and Sport. 2015;5(8):521-528. ISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.32287 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A521-528 https://pbn.nauka.gov.pl/works/657742 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 26.07.2015. Revised 05.08.2015. Accepted: 24.08.2015. Cele i zadania ogrodów zoologicznych The objectives and tasks of zoos Angelika Habel, Sławomir Mroczkowski1 1Zakład Genetyki i Podstaw Hodowli Zwierząt, Uniwersytet Technologiczno-Przyrodniczy im Jana i Jędrzeja Śniadeckich w Bydgoszczy Streszczenie Praca ogrodów zoologicznych regulowana jest przez podstawowe przepisy prawne. Z definicji ogród zoologiczny to instytucja, której działalność polega na przetrzymywaniu i ekspozycji żywych, dziko występujących gatunków zwierząt na widok publiczny. Najbardziej liczące się ogrody zoologiczne starają się spełniać wymagania narzucane przez przepisy prawne oraz realizować zadania związane z hodowlą zagrożonych gatunków zwierząt, edukacją ekologiczną, ochroną zwierząt, nauką oraz rekreacją. Sprawują one pieczę nad standardami opieki i dobrostanu zwierząt. W tym celu łączą swoje siły poprzez przynależność do organizacji zrzeszających ogrody zoologiczne na poziomie krajowym, europejskim oraz globalnym. Słowa kluczowe: ogród zoologiczny, zoo, hodowla dzikich zwierząt. Summary The work of zoos are regulated by basic legislation. By definition, the zoo is an institution whose business is to detention and exposure of living in the wild animal species on public view. The most the mainstream zoos are trying to meet the requirements imposed by legislation and perform tasks related to the breeding of endangered species, environmental education, animal welfare, science and recreation. They exercise custody of the standards of care and welfare. For this purpose they combine their strength through membership in organizations at national, European and global levels. Key words: zoo, breeding of wild animals.